Soil available phosphorus and pH are key factors affecting the site index of Larix kaempferi plantations in China - Wei, Hongyang; Chen, Dongsheng; Wu, Chunyan; Sun, Xiaomei; Zhang, Shougong (Frontiers in Forests and Global Change, 2024)
Assessing the quality of forest sites is crucial for evaluating the potential productivity of forests and formulating effective management strategies. Therefore, it is essential to understand how environmental variables affect the site quality. This study focuses on quantifying the effects of 44 dfferent environmental variables including climate, topography, soil properties on site index of Larix kaempferi plantations in three different climate regions in China, utilizing the random forest algorithm. L. kaempferi site index, determined from stem analysis data by felling dominant trees from 51 even-aged stands. The results indicated that the proposed random forest model explained approximately 59.47% of site index variations. Among many environmental variables, available phosphorus, pH, Degree-days above 5°C (DD5), spring mean maximum temperature (Tmax_MAM) had significant effects on site index (P < 0.05) and the importance of soil chemical properties generally exhibit relatively larger effects on site index than climate variables and topography variables. The partial dependence analysis revealed that the L. kaempferi plantations had maximum values at approximately 30mg/kg of available phosphorus in the first soil layers, 30mg/kg of available phosphorus in the second soil layers, 20mg/kg of available phosphorus in the third soil layers, the DD5 between 2600 ℃ and 3000℃ and Tmax_MAM approximately 15℃. Our findings attempt to provide a better understanding of the sitegrowth relationship.